Who writes the history of an age? - Stanford India Association; Association for India's Development (Bay Area Chapter); Graduate Student Council, Stanford University;:::Creator::::::::::::
Poster promoting a discussion with Professor K.N. Panikkar on the politics of rewriting history within the national context of India.